Non-invasive imaging of microcirculation: a technology review - Eriksson S (Dove Medical Press, 2014)
Sam Eriksson,1,2 Jan Nilsson,1,2 Christian Sturesson1,2 1Department of Surgery, Clinical Sciences Lund, Lund University, 2Skåne University Hospital, Lund, Sweden Abstract: Microcirculation plays a crucial role in physiological processes of tissue oxygenation and nutritional exchange. Measurement of microcirculation can be applied on many organs in various pathologies. In this paper we aim to review the technique of non-invasive methods for imaging of the microcirculation. Methods covered are: videomicroscopy techniques, laser Doppler perfusion imaging, and laser speckle contrast imaging. Videomicroscopy techniques, such as orthogonal polarization spectral imaging and sidestream dark-field imaging, provide a plentitude of information and offer direct visualization of the microcirculation but have the major drawback that they may give pressure artifacts. Both laser Doppler perfusion imaging and laser speckle contrast imaging allow non-contact measurements but have the disadvantage of their sensitivity to motion artifacts and that they are confined to relative measurement comparisons. Ideal would be a non-contact videomicroscopy method with fully automatic analysis software. Keywords: laser speckle contrast imaging, sidestream dark-field, orthogonal polarization spectral imaging, laser Dopplerimaging